2019
DOI: 10.1590/1980-57642018dn13-040005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the INECO Frontal Screening for detecting Mild Cognitive Impairment in Parkinson’s disease

Abstract: Cognitive deficits in Parkinson’s disease typically affect executive functions. Recently, the concept of Mild Cognitive Impairment (MCI) has been related to PD (PD-MCI). PD-MCI is considered a transition phase to Parkinson’s disease Dementia. Therefore, it is important to identify PD-MCI in a reliable way. Objective: To evaluate the sensitivity and specificity of the INECO Frontal Screening (IFS) in detecting cognitive deficits in PD-MCI. Additionally, we compare the IFS and the Addenbrook Cognitive Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…In the specific case of Cuba, we did not find any previous study that explored the clinical utility of FAB; conversely, to date, only one study in the country has investigated the sensitivity and specificity of IFS in detecting cognitive deficits in MCI patients (md-aM-CI). 17 Contrary to results of the present study, the previous study showed that IFS had a low capacity for discriminating between md-aMCI patients and healthy controls. This discrepancy accounts for differences in the cognitive profiles of the MCI patients included in both studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the specific case of Cuba, we did not find any previous study that explored the clinical utility of FAB; conversely, to date, only one study in the country has investigated the sensitivity and specificity of IFS in detecting cognitive deficits in MCI patients (md-aM-CI). 17 Contrary to results of the present study, the previous study showed that IFS had a low capacity for discriminating between md-aMCI patients and healthy controls. This discrepancy accounts for differences in the cognitive profiles of the MCI patients included in both studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This discrepancy accounts for differences in the cognitive profiles of the MCI patients included in both studies. In the study conducted by Broche-Pérez et al 17 the md-aMCI patients did not differ from healthy controls in the following subtests: Conflicting instructions (sensitivity to interference), Months backward, and Digit Span Task (working memory). In this sense, the md-aMCI patients of the present study show a greater executive deficit, which increases the sensitivity of IFS.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The maximum total score in the ACE-R is 100 points (see Supplementary Section 1). Furthermore, subjects' executive functioning was examined through the INECO Frontal Screening (IFS) (Torralva et al, 2009), a validated test to measure executive dysfunction in neurodegeneration (Gleichgerrcht et al, 2011;Broche-Pérez et al, 2019;Moreira et al, 2019). This test comprises the following eight subtests: (1) motor programming (Luria series, "fist, edge, palm"); (2) conflicting instructions (hitting the table once when the administrator hits it twice, or hitting it twice when the administrator hits it only once); (3) motor inhibitory control; (4) numerical working memory (backward digit span);…”
Section: General Cognitive State and Executive Functioningmentioning
confidence: 99%
“…To identify neuropsychological profiles with a prominent ED, it may be relevant to measure executive functions in more detail, as evidence has shown that a method specifically designed for detecting ED can better identify patients with dysexecutive profiles than general screening methods (Broche-Pérez et al, 2019; Fiorentino et al, 2013). Related to this, the Frontal Assessment Battery (FAB; Dubois et al, 2000) and the Institute of Cognitive Neurology (INECO) Frontal Screening (IFS; Torralva et al, 2009) are tools designed to assess executive functions and may be particularly useful in the early detection of EOD, especially considering the prominence of ED in EOD.…”
Section: Introductionmentioning
confidence: 99%